Horizontaland vertical spillovers from FDI: Evidence from panel data for the Italian manufacturing sector - Reganati, Filippo; Sica, Edgardo (Journal of Business Economics and Management, 2007)
Foreign direct investment (FDI) from Multinational Enterprises (MNEs) can be beneficial to host countries, since it may generate positive externalities to domestic firms, contributing to the increase of their productivity. These positive effects can take place both within an industry (“horizontal” spillovers) and across industries (“vertical” spillovers) as in the case of technology transfers to domestic suppliers or customers in the production chain. Using a firm‐level panel data, in this paper we analyse productivity spillovers from FDI in the Italian manufacturing firms both within and across industries. Our results suggest the existence of “vertical” spillovers and no evidence of “horizontal” ones.First Published Online: 14 Oct 2010